If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Simplifying b^{3}+ 49b = 0 Reorder the terms: 49b + b^{3}= 0 Solving 49b + b^{3}= 0 Solving for variable 'b'. Factor out the Greatest Common Factor (GCF), 'b'. b(49 + b^{2}) = 0## Subproblem 1

Set the factor 'b' equal to zero and attempt to solve: Simplifying b = 0 Solving b = 0 Move all terms containing b to the left, all other terms to the right. Simplifying b = 0## Subproblem 2

Set the factor '(49 + b^{2})' equal to zero and attempt to solve: Simplifying 49 + b^{2}= 0 Solving 49 + b^{2}= 0 Move all terms containing b to the left, all other terms to the right. Add '-49' to each side of the equation. 49 + -49 + b^{2}= 0 + -49 Combine like terms: 49 + -49 = 0 0 + b^{2}= 0 + -49 b^{2}= 0 + -49 Combine like terms: 0 + -49 = -49 b^{2}= -49 Simplifying b^{2}= -49 The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.## Solution

b = {0}

| a^2+7ab+10b^2= | | 7(6x-3)=29 | | -4(2x-10)+3=-10 | | 10x+5y=-15 | | 6x+1=26-2x | | 14-9x=3x-70 | | 6x+31=8x+13 | | -4(7-2s)=11 | | 6x-(2x+5)=19 | | 8x^2+5x-6=0 | | 6x+38=74 | | 7x-19=-2 | | 7+3x=23+x | | x+7=19+2x | | 8x+18=58 | | 2x^2-72=0 | | x^2+23+60=0 | | 3x^2+18x-27=0 | | 5a+6=2a+20 | | 8x-16=40 | | 0-5x=14-17x | | 3+7x=75+x | | -13-5x=12-10x | | 4-6x=13-7x | | -17-7x=10x+17 | | x^2+13-17=0 | | 5x^2+10x+5=0 | | 14-10x=46-38x | | -104-10x=8x+22 | | 25x+23=17x+1 | | 75-3x^2=0 | | 10-9x=127-30x | | x^3+25= | | 121-6x=2x+17 | | 50x^2=98x | | 4x+7=-101-8x | | -15-8x=10x+21 | | 10-7x=29-14x | | 8x^3+20x^2+12=0 | | 79-7x=11x+23 | | 100x^2-100x-600=0 | | 12x+18=4x+234 | | 2(k-4)=0.5(4k-16) | | 3s+12+s=-10+6s-8 | | 8x^2+44x+60=0 | | 4x^3+8x^2-3x=6 | | 6x^4-10x^3-6x^2=0 | | 2x^3-6x^2+2x=0 | | 25x^3+20x^2+3x=0 | | 5x*2+10x+5=0 | | X^2-18x*81=0 | | x^5-81x^4=0 | | 3x^3-6x^2-72x=0 | | 12(x+8)=48(x+2) | | 6=0.24x | | 6x-3y=9 | | 20x-10=4x+54 | | X^3+4x^2+6x=0 | | x^4-29x^2=-100 | | 5x+9=7x+5 | | 3x^2+x=0 | | 2(4)=3(10)z+2 | | 2m+13=3m-7 | | 23+6q=53 | | 60x^2-130x+60=0 |